Pengantar filsafat / K. Bertens, Johanis Ohoitimur, Mikhael Dua; editor, Widiantoro - Bertens, K. ; Ohoitimur, Johanis ; Mikhael Dua ; Widiantoro (Kanisius, 2018)
xii, 428 halaman : ilustrasi ; 24 cm.